Structures and mechanism of transcription initiation by bacterial ECF factors. Issue 13 (27th May 2019) - Fang, Chengli; Li, Lingting; Shen, Liqiang; Shi, Jing; Wang, Sheng; Feng, Yu; Zhang, Yu
Abstract: Bacterial RNA polymerase (RNAP) forms distinct holoenzymes with extra-cytoplasmic function (ECF) σ factors to initiate specific gene expression programs. In this study, we report a cryo-EM structure at 4.0 Å of Escherichia coli transcription initiation complex comprising σ E —the most-studied bacterial ECF σ factor ( Ec σ E -RPo), and a crystal structure at 3.1 Å of Mycobacterium tuberculosis transcription initiation complex with a chimeric σ H/E ( Mtb σ H/E -RPo). The structure of Ec σ E -RPo reveals key interactions essential for assembly of E. coli σ E -RNAP holoenzyme and for promoter recognition and unwinding by E. coli σ E . Moreover, both structures show that the non-conserved linkers (σ2 /σ4 linker) of the two ECF σ factors are inserted into the active-center cleft and exit through the RNA-exit channel. We performed secondary-structure prediction of 27, 670 ECF σ factors and find that their non-conserved linkers probably reach into and exit from RNAP active-center cleft in a similar manner. Further biochemical results suggest that such σ2 /σ4 linker plays an important role in RPo formation, abortive production and promoter escape during ECF σ factors-mediated transcription initiation.